Evaluasi efektifitas effective microorganism-4 (EM-4) dalam menaikkan volume produksi biogas - Tira, H.S.; Syahrul, S.; Umbara, E.G. (Dinamika Teknik Mesin, 2018)
Anaerobic digestion process of cow dung was observed over 30 days with addition of effective microorganism – 4 in regard to improve biogas volume production. Temperature for biogas production was kept constant and was conducted at mesophilic mode. It was found that EM-4 addition was effective to increase the biogas yields production. The improvement in biogas volume was recorded as high as 87.8% which was achieved in 10% v/v EM-4 addition. However, the solution concentration should be limited in certain amount. By experimentally work, the results showed that adding more EM-4 into digestate resulted in reduction of biogas volume gradually. The most influential factor of the result may be attributed by the alteration of digestate pH from netral to more acidic. This acidic condition hampered microorganism to do anaerobic process well.